Examination of the Relationship Between Adolescents' Social Anxiety, Cognitions, and Attitudes - Huseyin Unubol; Gokben Hizli Sayar; Elif Gul (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The purpose of this study is the investigation of the relationship between cognitive distortions and non-functional attitudes of adolescences, their social appearance concerns, and social comparison levels. Study sample comprises 319 high school students from Arnavutkoy District of the City of Istanbul. Study data were obtained using Dysfunctional attitude scale, Cognitive distortion in interpersonal relations scale, social appearance anxiety scale, social comparison scale  and the demographics form created by the author. Data collected were analyzed using SPSS 21 software package. Spearman Correlation Analysis was used to analyze the relationship between scores that obtained from scales. T-test and Kruskal Wallis Test were used to compare the scores that obtained from scales. Study Findings suggest that adolescents' nonfunctional attitude scale scores are associated with cognitive distortions, social anxiety, and social comparisons. It has been observed that the need for approval and perfectionist attitude play a very central role in the cognitive distortions of adolescents. It is also noteworthy that these attitudes are the only relationship we have in our comparison with others. Social anxiety has been found to be strongly associated with both our cognitive distortions in relation to others, as well as all nonfunctional attitudes. Avoidance of intimacy and non-realistic relationship expectation from cognitive distortions have a strong relationship with perfectionist attitude and need for approval. This study reports the central role of perfectionist attitude and need for approval in relation to social anxiety and social comparison to different attitudes and cognitive distortions. [JCBPR 2018; 7(2.000): 53-61]